2024
DOI: 10.1098/rspb.2023.1408
|View full text |Cite
|
Sign up to set email alerts
|

Temporal cluster-based organization of sleep spindles underlies motor memory consolidation

Arnaud Boutin,
Ella Gabitov,
Basile Pinsard
et al.

Abstract: Sleep benefits motor memory consolidation, which is mediated by sleep spindle activity and associated memory reactivations during non-rapid eye movement (NREM) sleep. However, the particular role of NREM2 and NREM3 sleep spindles and the mechanisms triggering this memory consolidation process remain unclear. Here, simultaneous electroencephalographic and functional magnetic resonance imaging (EEG-fMRI) recordings were collected during night-time sleep following the learning of a motor sequence task. Adopting a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
(148 reference statements)
0
1
0
Order By: Relevance
“…Specifically, procedural memory (Schönauer et al, 2014), but also declarative and emotional memories were shown to benefit from sleep between learning and recall, with slow wave sleep (SWS) benefiting declarative memories more while rapid eye movement sleep enhances procedural and emotional memory (Diekelmann et al, 2009). Furthermore, sleep spindles were associated with better procedural memory consolidation (van Schalkwijk et al, 2020;Kumral et al, 2023;Boutin et al, 2024).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, procedural memory (Schönauer et al, 2014), but also declarative and emotional memories were shown to benefit from sleep between learning and recall, with slow wave sleep (SWS) benefiting declarative memories more while rapid eye movement sleep enhances procedural and emotional memory (Diekelmann et al, 2009). Furthermore, sleep spindles were associated with better procedural memory consolidation (van Schalkwijk et al, 2020;Kumral et al, 2023;Boutin et al, 2024).…”
Section: Introductionmentioning
confidence: 99%